2007
DOI: 10.3354/meps333195
|View full text |Cite
|
Sign up to set email alerts
|

Statolith microchemistry traces the environmental history of the boreoatlantic armhook squid Gonatus fabricii

Abstract: Statoliths of the gonatid squid Gonatus fabricii from Disko Bay, West Greenland, were analysed by laser ablation inductively coupled plasma mass-spectrometry (LA-ICP-MS) to determine the concentrations and spatial distributions of 9 minor and trace elements (Sr, Ba, Mg, U, Zn, Mn, Y, Zr, Na). Element composition was assigned in situ to distinct statolith regions, corresponding to ontogenetic stages of an individual squid's life. Significant variations in concentrations of all measured elements except Na were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 52 publications
3
29
0
Order By: Relevance
“…The only other known study that tested the effects of environmental pH on squid-embryo statolith geochemistry found that only 65 Zn significantly differed from an elemental suite that included 110m Ag, 109 Cd, 57 Co, 203 Hg and 54 Mn [49]. Evidence that environmental tracers in squid statoliths can track seawater pH and [O 2 ] is especially useful, because uranium has been shown to be promising for understanding squid life history, migrations and habitat use [88,90,91].…”
Section: Discussionmentioning
confidence: 99%
“…The only other known study that tested the effects of environmental pH on squid-embryo statolith geochemistry found that only 65 Zn significantly differed from an elemental suite that included 110m Ag, 109 Cd, 57 Co, 203 Hg and 54 Mn [49]. Evidence that environmental tracers in squid statoliths can track seawater pH and [O 2 ] is especially useful, because uranium has been shown to be promising for understanding squid life history, migrations and habitat use [88,90,91].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated Ba/Ca in otoliths and invertebrate hard parts has been associated with upwelling (Lea et al 1989;Patterson et al 1999;Zacherl 2005;Brown 2006) and deep water (Zumholz et al 2007). Dissolved Ba in oceanic waters shows a nutrient-like distribution with very low concentrations in surface waters and higher values in deep water (Chan et al 1977).…”
Section: Discussionmentioning
confidence: 99%
“…For example, oxygen isotopes in squid statoliths are deposited in equilibrium with ambient waters (Radtke 1983). Variation in strontium (Sr) concentrations within statoliths track squid in ontogenetic migrations (Yatsu et al 1998, Ikeda et al 2003, Zumholz et al 2007, vertical diel migrations (Ikeda et al 1998, Bettencourt & Guerra 2000, and daily feeding activities (Ikeda et al 2002a). Recent work has also indicated distinct seasonal, developmental, and spatial patterns of chemical signatures in statoliths of Doryteuthis (= Loligo) gahi in the south Atlantic (Arkhipkin et al 2004).…”
Section: Introductionmentioning
confidence: 99%